2020
DOI: 10.1088/1755-1315/518/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Lignification on Potatoes by Application of Trichoderma viride

Abstract: Leaf blight disease caused by pathogenic fungus Phytophthora infestans is the major disease in potato that can reduce its production up to 100%. The use of biological agent Trichoderma viride as an inducing potato resistance against leaf blight disease has been considered potential method. The purpose of this study was to evaluate the use of biological agent Trichoderma viride in inducing potato plant resistance against late blight by Phytopthora infestans. Research on induced resistance was conducted in a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For example, in olive plantations, ''Olive Quick Decline Syndrome'' tolerant cultivar has been shown to decrease in disease progression through lignification of cell wall against X. fastidiosa (Sabella et al 2018). Similarly, in potatoes, leaf xylem tissue lignifications (induced by the biocontrol fungus Trichoderma viride) have been found to decrease the severeness of late blight disease (Purwantisari et al 2020). The various biochemical metabolites and cell wall components that have major contributions to disease resistance in different crops are presented in Table 3.…”
Section: Lignin Depositionmentioning
confidence: 99%
“…For example, in olive plantations, ''Olive Quick Decline Syndrome'' tolerant cultivar has been shown to decrease in disease progression through lignification of cell wall against X. fastidiosa (Sabella et al 2018). Similarly, in potatoes, leaf xylem tissue lignifications (induced by the biocontrol fungus Trichoderma viride) have been found to decrease the severeness of late blight disease (Purwantisari et al 2020). The various biochemical metabolites and cell wall components that have major contributions to disease resistance in different crops are presented in Table 3.…”
Section: Lignin Depositionmentioning
confidence: 99%
“…Electron microscopy demonstrated substantial morphological and ultrastructural malformations in T. atroviride VOC-treated hyphae, including cell deformation, collapse, and organelle disintegration. Purwantisari et al [76] reported T. viride induced resistance in potato plants against late blight. Cwalina-Ambroziak et al [77] found that using an integrated chemical and biological approach decreased the symptoms of P. infestans infections.…”
Section: Discussionmentioning
confidence: 99%
“…It also promoted growth, yield characteristics and quality of potato crop. The effect of the antagonist here has been evaluated as a biofertilizer, increasing the activity of nutrients in the potato root zone (Molla et al, 2012;Purwantisari et al, 2018).…”
Section: The Effect Of Antagonist Microorganisms On the Host Plant In...mentioning
confidence: 99%